Pengaruh Juri, Prestasi Sebelumnya dan Tingkat Institusi Terhadap Penilaian dalam Lomba Web-Site Lingkup Kementrian Pertanian - Edi Abdurachman (Bina Nusantara University, 2010)
In promoting the use of Information and Communication Technology (ICT) in order to improve efficiency and effectiveness of government service institutions, the Government of Indonesia issued Presidential Instruction No. 3 of 2003 on e-Government. The directive requested that all government institutions in Indonesia should take advantage of ICT to improve public services. In line with this, the Ministry of Agriculture has launched several efforts to support the implementation of Presidential Instruction. One of these efforts is the implementation of the Web Site Competition between Work units under the Ministry. The contest has been held since 2004. The participants were grouped into three categories: 1. Directorate General / Agency 2. Provincial Agricultural Office 3. District Agriculture Office. To carry out the website competition, the Ministry of Agriculture has appointed a five person jury. To evaluate whether there are significant differences between the judges in scoring on the website which was considered and the factors that may affect the assessment, some analysis has been done. The variables included in the analysis was judge scores, level of institution, previous achievements in the competition, the location of both institutions in Java and outside Java. The statistical methods used in the analysis are Multiple Linear Regression and Variance Analysis. The analysis uses data from the Ministry of Agriculture Web Site Competition 2008-2010.